2018
DOI: 10.1002/pits.22216
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind, directly and indirectly, facilitates kindergarten adjustment via verbal ability, executive function, and emotion knowledge

Abstract: Theory of mind describes the ability to engage in perspective‐taking, understand intentions, and predict actions and emotions. Theory of mind typically achieves major developmental milestones around age of 5, coinciding with the transition to kindergarten, and is associated with a verbal ability (receptive and expressive vocabulary), executive function (inhibitory control and working memory), and emotion knowledge. Less is known about how the theory of mind operates in low‐income samples, where foundational sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
(90 reference statements)
3
13
0
Order By: Relevance
“…For instance, Grazzani et al (2016b) found that stimulating conversations about mental states in young children attending nursery school had positive effects on their emotion knowledge and theory of mind skills which remained stable over time. In turn, improved social cognition is associated with multiple positive outcomes, such as good peer relationships, popularity with peers, prosocial behaviors (Imuta et al, 2016; Ornaghi et al, 2016), school readiness, and adjustment (Wang, 2015; Brock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Grazzani et al (2016b) found that stimulating conversations about mental states in young children attending nursery school had positive effects on their emotion knowledge and theory of mind skills which remained stable over time. In turn, improved social cognition is associated with multiple positive outcomes, such as good peer relationships, popularity with peers, prosocial behaviors (Imuta et al, 2016; Ornaghi et al, 2016), school readiness, and adjustment (Wang, 2015; Brock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a slightly older sample, the mean correlation between receptive vocabulary and emotion knowledge was r = 0.51 (12). Brock et al (13) reported a zero-order correlation of r = 0.40 between emotion knowledge and expressive vocabulary in 5-year-olds. These studies suggest that language skills are very important when acquiring the basic knowledge about emotions before entering formal schooling.…”
Section: Emotion Knowledge Language Skills and Executive Functionsmentioning
confidence: 93%
“…These experiences foster opportunities to recognise and discuss emotions, as well as to discuss inner states. Interventions such as these have been shown to have positive long-term effects on peer relationships, popularity with peers, school readiness, and general life adjustment (Brock, Kim, Kelly, Mashburn, & Grissmer, 2019;Imuta, Henry, Slaughter, Selcuk, & Ruffman, 2016).…”
Section: Implications For Practicementioning
confidence: 99%